TINJAUAN TATA RIAS PENGANTINDI KECAMATAN KOTO TANGAH PADANG SUMATERA BARAT - Yosa, Efrimai; Rahmiati, Rahmiati; Astuti, Murni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was done from there have been many changes both in makeup and fashion that used bride in procession of marriage at Koto Tangah Padang. Where the bride's clothes that used to be red can be replaced with various colors. For kodek / lambak / sarong do not use songket anymore but velvet fabric which is adjusted to the color of the wedding dress and then in add the tail of the long cloth resembles the selayar at the Western wedding. This research was conducted with the aim to describe bridal makeup in District Koto Tangah Padang, West Sumatra. The method used is descriptive method with qualitative approach. Data collection in this research is done by using interview technique, observation, documentation recording, and photo. The results showed the results as follows: 1) The results of bridal makeup in Kecamatan Koto Tangah Padang is no different from Minangkabau bride makeup in general. 2) The form of clothing used by the bride in Koto Tangah Padang is not different from Minangkabau wedding dress in general. 3) The difference of fashion and bridal accessories in the past (before 2000) and currently lies from the modifications made by the wedding and customer wishes.Keywords: bridal makeup, wedding dress, bridal accessories